(untitled) (Nexus International Journal of Science and Education, 2024)
This qualitative study investigated the lived experiences of 12 teachers who explored mindfulness-based practices to reduce stress and anxiety. The study aimed to achieve three primary objectives. First, it sought to understand how teachers experienced exploring mindfulness-based practices for stress and anxiety reduction. This focus included mindfulness-based interventions, teacher well-being, and their impact on educational outcomes. Second, the study examined how teachers coped with the challenges associated with mindfulness-based practices. It identified themes related to past experiences of stress and anxiety management, the effectiveness of mindfulness interventions they had tried, and the promotion of teacher well-being. Finally, the study delved into the educational insights and practices derived from exploring mindfulness. This focus centered on educational settings, professional development opportunities, and potential improvements in student engagement. Through in-depth interviews with the participants, the study uncovered nuanced experiences, shedding light on the transformative impact that mindfulness-based practices could have. Teachers' narratives revealed the mindfulness techniques they employed to manage stress and anxiety, highlighting their effectiveness in enhancing overall well-being. The findings provided valuable insights into the challenges faced by teachers, the coping mechanisms they used, and the transformative impact on both teacher well-being and student engagement. These insights have significant implications for educational management, advocating for the integration of mindfulness practices to foster a positive and supportive learning environment.